The Efficacy of Rapid Counseling with Single-Session Music Therapy on Enhancing Emotion Regulation in Response to Activating Events - Oentarto, Aloysius Selo Aryobimo (Buletin Konseling Inovatif, 2026)
This study examines the efficacy of Rapid Counseling with Single-Session Music Therapy (RCSSMT) in enhancing emotion regulation in response to activating events. Many daily circumstances are uncontrollable, often leading individuals with negative thought patterns to experience distress and anxiety, known as activating events. Music therapy, as a holistic approach, acts as an emotion-focused coping strategy by calming physiological stress responses and preparing the individual for cognitive restructuring. This research employed a single-subject pre-test, post-test, and follow-up design, with the subject being SG, who had the lowest initial score on the Emotion Regulation Questionnaire. The scores showed a gradual but significant improvement: Pretest: 37 (Medium), Posttest: 44 (Medium), and Follow-Up (two months later): 67 (High). This peak score at follow-up suggests that music functions as an emotional bridge, successfully facilitating the Cognitive Reappraisal process over time, which is crucial for adaptive recovery and strengthening psychological resilience. The findings conclude that RCSMT is an effective intervention for improving an individual's emotional regulation abilities in the face of stressful activating events.